PENGARUH KESADARAN MEREK DAN PENGALAMAN MEREK TERHADAP KEPUASAN PELANGGAN (Studi Pada Kegiatan Brand Activation Merek Marina) - Stepahanus Ariowibowo; Imam Wibowo; Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This study is about The Effect of Kesadaran merek and Brand Experience on Kepuasan pelanggan of Marina brand activation. This study aims to determine the simultaneous and partial effect between kesadaran merek and brand experience on consumer satisfaction of Marina brand activation in Bandung. In this study the sample took 50 respondents using saturation sampling technique, where all of the population became sample. The data that has been obtained tested using multiple linear regression analysis techniques. The results that shown from this study are kesadaran merek and brand experience simultaneous and partial gave positive and significant effect on kepuasan pelanggan, where brand experience has a more dominant effect to kepuasan pelanggan. Thus, it can be concluded that kesadaran merek and brand experience influence kepuasan pelanggan of Marina brand activation participants in Bandung.